A Large Extragnathic Keratocystic Odontogenic Tumour - Soumya Makarla; Radhika M. Bavle; Sudhakara Muniswamappa; Srinath Narasimhamurthy (Case Reports in Pathology)
Odontogenic keratocysts (OKCs) are developmental cysts which occur typically in the jawbones. They present more commonly in the posterior mandible of young adults than the maxilla. OKCs have been reclassified under odontogenic tumours in 2005 by the WHO and have since been termed as keratocystic odontogenic tumours (KCOTs). Here we report a case of a recurrent buccal lesion in a 62-year-old man which was provisionally diagnosed as a space infection (buccal abscess) but surprisingly turned out to be a soft tissue KCOT in an unusual location on histopathologic examination.